DETERMINATION OF THE RELATIONSHIP BETWEEN THE CHANGE OF THE MOTION MODES OF THE WORKING ARRAY AND THE DESIGN FEATURES OF THE "TURBULA" TYPE TURNING MACHINE - ZALYUBOVSKYI, Mark; PANASYUK, Igor; KOSHEL, Olexandr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Using the SolidWorks automated design system, analytical studies of the "Turbula" type rolling machine with an additional movable rocker link with a vertical axis of rotation were carried out for the possibility of determining the dependence between the change in the movement modes of the working array and the design features of this rolling machine. It is noted that the movement of the working array in the filling tanks with different types of movement can be carried out in cascade, waterfall, mixed, as well as closed modes of movement. During the implementation of each mode of movement of the working array, conditions are created for the performance of appropriate felting technological operations or mixing of loose fine-dispersed substances. It was established that the change in the modes of movement of the working array in the rolling container performing complex spatial movement depends on three factors - the large-scale standard size of the rolling machine, the angular velocity of the drive shaft and the ratio of the interaxial distance of the container to the interaxial distance of the forks, which is characterized by the coefficient λ, the relationship is established the relationship between these factors. Mathematical dependencies have been obtained to determine the maximum angular speed of the drive shaft of the "Turbula" type rolling machine with an additional movable rocker link with a vertical axis of rotation, which will correspond to the implementation of the necessary mode of movement of the working array, when it moves in a given capacity. The obtained results of analytical studies can be used in the relevant design bureaus of machine-building enterprises at the stage of designing rolling equipment with complex spatial movement of working capacities.